2010
DOI: 10.1016/j.autneu.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Paraventricular nucleus modulates autonomic and neuroendocrine responses to acute restraint stress in rats

Abstract: The paraventricular nucleus of the hypothalamus (PVN) has been implicated in several aspects of neuroendocrine and cardiovascular control. The PVN contains parvocellular neurons that release the corticotrophin release hormone (CRH) under stress situations. In addition, this brain area is connected to several limbic structures implicated in defensive behavioral control, as well to forebrain and brainstem structures involved in cardiovascular control. Acute restraint is an unavoidable stress situation that evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 54 publications
3
46
0
4
Order By: Relevance
“…The fast frame rate of the thermal videoing technique was able to show a drop in eye-region temperature of approximately 2 °C in 10 sec followed by a subsequent rise in temperature to within 0.5 °C of baseline within 3 min. Although peripheral cooling in response to mild stress has been recorded previously at around 1 min intervals 17,26,32 , the technique here showed that maximum drop in temperature may be extremely rapid. With lower time resolution the magnitude of this effect may be missed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The fast frame rate of the thermal videoing technique was able to show a drop in eye-region temperature of approximately 2 °C in 10 sec followed by a subsequent rise in temperature to within 0.5 °C of baseline within 3 min. Although peripheral cooling in response to mild stress has been recorded previously at around 1 min intervals 17,26,32 , the technique here showed that maximum drop in temperature may be extremely rapid. With lower time resolution the magnitude of this effect may be missed.…”
Section: Discussionmentioning
confidence: 97%
“…In response to a well-established acute mild stressor to an animal we expected rapid changes in the pattern of blood flow, from the periphery to the core via sympathetically mediated vasoconstriction that reduces skin temperature 17 . The periorbital region was chosen as this provided the only region of the body that was uninsulated and is associated with a rich intermingled network of small blood vessels, the rete ophthalmicum that can affect the heat loss from the eye 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that this mechanism might have two functions; to redistribute blood to more important organs (e.g. the muscles and brain) and to prevent blood loss owing to potential injuries in the peripheries [26]. Decreased surface body temperature has been found in response to apparent emotional stress in sheep [27] and cattle [18].…”
Section: Discussionmentioning
confidence: 99%